(Invited) Cavity-Free Micro Thermoelectric Energy Harvester with Si Nanowires. (23rd April 2019) - Watanabe, Takanobu; Tomita, Motohiro; Zhan, Tianzhuo; Shima, Keisuke; Himeda, Yuya; Yamato, Ryo; Matsukawa, Takashi; Matsuki, T.
Abstract : We present a new design of silicon-based micro thermoelectric generator, which utilizes silicon nanowire as the thermoelectric leg. It is driven by a steep temperature gradient exuding around a heat flow perpendicular to the substrate, and the silicon nanowires are not suspended on a cavity etched on the substrate. The power density is scalable by shortening the silicon nanowire to sub-μm length, which was experimentally demonstrated and tens of µW/cm 2 -class power generation was achieved at an externally applied temperature difference of only 5 K. A numerical discussion shows that the thermoelectric power can be drastically enhanced by suppressing the thermal resistance at the entire substrate. Thus, there is a plenty of room at the micro or submicrometric scales for realizing thermal energy harvesting devices with high power densities.